P434 The PROPER study: interim analysis of a Pan-European real-world study of SB5 adalimumab biosimilar after transition from reference adalimumab in patients with Crohn's disease. (21st January 2022) - Dignass, A U; Gisbert, J P; Bossa, F; Freudensprung, U; Addison, J
Abstract: Background: SB5, a biosimilar to reference adalimumab (ADL), received EU marketing authorisation in August, 2017, based on pre-clinical and clinical phase I and III studies that demonstrated bioequivalence and comparable efficacy, safety and immunogenicity profiles to ADL. The real-world study 'PROPER' is designed to provide insights into outcomes of the transition from reference to SB5 outside the controlled, randomised, clinical trial setting. Under an umbrella design, 1000 patients with immune-mediated inflammatory disease have been enrolled at centres in Belgium, Germany, Ireland, Italy, Spain and the UK. Methods: Eligible patients had been transitioned to SB5 as part of routine treatment following a minimum of, 16 weeks' treatment with ADL. Data were captured from patient charts retrospectively for, 24 weeks prior to and prospectively and/or retrospectively for, 48 weeks after SB5 initiation. This interim analysis of the Crohn's disease cohort reports outcome measures including clinical characteristics, disease activity, persistence on SB5, clinical management and safety for patients enrolled at, 32 specialist sites and followed up to the data extract date of October, 5 th, 2021. Results: Of the, 462 patients included in this interim analysis, the majority were enrolled in Germany (n=127), Spain (n=118) and Italy (n=79); Belgium, Ireland and UK enrolled, 56, 46 and, 36 patients, respectively. At time of data extract, 416 patients had completed, 48 weeks of follow-up and, 15 had withdrawn from the study. The most common reasons driving transition were physician decision, or a mandate from the health authority or payer. At baseline, the majority of patients were in remission or had mild disease as determined by Harvey Bradshaw Index (HBI), and were in remission or stable according to physician opinion. Most patients transitioned to the same SB5 regimen as they had received for ADL (Table 1). Twenty-four patients reported, 27 serious adverse events (SAE), of which, 4 (anal fistula [n=1], perianal abscesses [n=2] and subileus [n=1]) were considered by the study physician to be related to SB5 administration. Conclusion: No meaningful change in HBI or SB5 dosing regimen was observed from baseline to Week, 48 after transition from ADL. The number of patients experiencing a treatment-related SAE was low, and no new safety concerns were detected. Thus, transition from ADL to SB5 was generally safe and effective in patients with Crohn's disease over, 48 weeks of follow-up. Acknowledgements: This study was funded by Biogen International GmbH. Statistical services were provided by FGK Clinical Research GmbH, Munich, Germany. Data management services were provided by Worldwide Clinical trial, Research Triangle Park, NC, USA.